2022
DOI: 10.7150/jca.64846
|View full text |Cite
|
Sign up to set email alerts
|

A Concise Review of MicroRNA-383: Exploring the Insights of Its Function in Tumorigenesis

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that commonly have 18-22 nucleotides and play important roles in the regulation of gene expression via directly binding to the 3'-UTR of target mRNAs. Approximately 50% of human genes are regulated by miRNAs and they are involved in many human diseases, including various types of cancers. Recently, microRNA-383 (miR-383) has been identified as being aberrantly expressed in multiple cancers, such as malignant melanoma, colorectal cancer, hepatocellular cancer, and gli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 120 publications
0
8
0
Order By: Relevance
“…In CRC cells, the enforced expression of miR-383 inhibited cell migration and proliferation by attenuating APRIL expression ( Cui et al, 2018 ). Figure 1 shows some gene targets of miR-383 and their function in cancer cell proliferation, EMT, invasion, and metastasis ( Yi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In CRC cells, the enforced expression of miR-383 inhibited cell migration and proliferation by attenuating APRIL expression ( Cui et al, 2018 ). Figure 1 shows some gene targets of miR-383 and their function in cancer cell proliferation, EMT, invasion, and metastasis ( Yi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have demonstrated that miR-383 mediates cellular proliferation via regulating the expression pattern of proliferation-associated genes i.e. Cyclin D1 (Yi et.al, 2022). Cyclin D1 is well known in regulating cell proliferation and has been demonstrated to be over expressed in several cancers (Qie S et.al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation, migration and angiogenesis of glioma-exposed endothelial cells were repressed via miR-383-VEGF/VEGFR2-FAK/Src signaling pathway [33]. On the other hand, a few studies identi ed miR-383 as an oncogene, which was highly expressed in cholangiocarcinoma, renal cell carcinoma, epithelial ovarian cell lines and so on [27]. However, the expression le and biofunction of miR-383 in osteosarcoma remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-383 acts as a tumor suppressor and is downregulated in various cancers [22][23][24][25][26]. This miRNA was reported can inhibit tumors from various phenotypes, including proliferation, differentiation, invasion and metastasis [27].…”
Section: Introductionmentioning
confidence: 99%